Antimicrobial and Antiinflammatory Activity of the Hydrogels Containing Rutin Delivery - Soni, Himesh; Malik, Jitender; Singhai, A.K.; Sharma, Sarvesh (Asian Journal of Chemistry, 2013)
Flavonoids are principal active constituents have been used to treatment of various human diseases. Rutin (quercetin-3-rhamnosyl glucoside) as the flavonoids display anticancer, antiviral, antiinflammatory and heart disease protective activities. Rutin by acting as antioxidants exhibited several beneficial effects, such as antiinflammatory, antiallergic, antiviral as well as an anticancer activity. The objective of present study was to formulate hydrogels containing rutin at various concentrations i.e., 0.020, 0.025 and 0.030 % (w/w). Hydrogels were prepared using Carbopol 934 and a methanolic (co-solvent) dispersion of rutin. The hydrogels were subjected to antimicrobial and antiinflammatory activity. The zone of inhibition of rutin in hydrogel systems was evaluated by cup plate method against bacteria i.e., Staphylococcus aureus, Staphylococcus glurance and Eschericia coli. The antiinflammatory activity of the hydrogel systems was also carried out by Carrageenan-induced rat paw edema model. Results of in vivo activity led to the conclusion that the hydrogel H2 formulation showed predominantly significant activity, which is comparable to the standard drug.